2018
DOI: 10.1002/cpdd.421
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 1, Randomized, Placebo‐ and Active‐Controlled Crossover Study to Determine the Effect of Single‐Dose Ertugliflozin on QTc Interval in Healthy Volunteers

Abstract: Ertugliflozin, a selective sodium-glucose cotransporter-2 inhibitor, is being developed for the treatment of type 2 diabetes mellitus. This randomized, 6-sequence, 3-period crossover study assessed the effect of ertugliflozin (100 mg; supratherapeutic dose) vs placebo and moxifloxacin (400 mg; positive control) on the QT interval corrected for heart rate (QTc) in 42 male or female healthy subjects. Triplicate electrocardiograms were performed predose and serially over 48 hours postdose in each treatment period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…This phase 1 study enrolled healthy subjects and evaluated the PK of ertugliflozin. The PK findings reported here in Chinese subjects residing in China are comparable with those observed in other populations [15][16][17][18][19][20][21][22] and are supported by results from a recently conducted phase 3 study exploring the efficacy and safety of ertugliflozin in Asian patients with T2DM. 32 This longer-term study (with the same ertugliflozin doses of 5 mg and 15 mg assessed in the current phase 1 study) demonstrated that ertugliflozin improved glycemic control and reduced body weight and systolic blood pressure in Asian patients with T2DM inadequately controlled on metformin monotherapy, including Chinese patients from mainland China.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This phase 1 study enrolled healthy subjects and evaluated the PK of ertugliflozin. The PK findings reported here in Chinese subjects residing in China are comparable with those observed in other populations [15][16][17][18][19][20][21][22] and are supported by results from a recently conducted phase 3 study exploring the efficacy and safety of ertugliflozin in Asian patients with T2DM. 32 This longer-term study (with the same ertugliflozin doses of 5 mg and 15 mg assessed in the current phase 1 study) demonstrated that ertugliflozin improved glycemic control and reduced body weight and systolic blood pressure in Asian patients with T2DM inadequately controlled on metformin monotherapy, including Chinese patients from mainland China.…”
Section: Discussionsupporting
confidence: 88%
“…19 The terminal elimination half-life (t ½ ) of ertugliflozin ranges from 11 to 17 hours. 5,6,[15][16][17][18][19][20][21][22] The PK of ertugliflozin are similar in healthy subjects and in patients with T2DM. 20 The major clearance pathway of ertugliflozin is metabolism via glucuronidation (86%) with minor contribution from oxidative metabolism (12%).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…To evaluate the potential effects of a supratherapeutic dose of ertugliflozin on prolongation of the cardiac QT interval, a randomized, three-treatment, six-sequence, three-period, crossover, placebo-and active-controlled study was conducted in 42 healthy subjects where fasted subjects received a single oral dose of ertugliflozin 100 mg (~ 6.7-fold greater than the highest ertugliflozin dose of 15 mg used in phase III studies), moxifloxacin 400 mg as a positive control, or placebo [45]. Following treatment with ertugliflozin, the maximum least squares mean (90% CI) difference in QT interval corrected for heart rate (QTc) using the Fridericia correction (QTcF) observed between ertugliflozin and placebo was 2.99 ms, which was less than the threshold of potential clinical concern of 5 ms.…”
Section: Thorough Qtc Studymentioning
confidence: 99%
“…Detailed methodology for the ertugliflozin and metformin assay procedures have been previously published. 9,23 The following plasma ertugliflozin and metformin PK parameters were calculated for each subject for each treatment using noncompartmental analysis of plasma concentration-time data: C max , t max , area under the plasma concentration-time profile from time 0 to the time of the last quantifiable concentration (AUC last ), AUC inf , and t 1/2 . Samples below the LLOQ were set to zero for analysis.…”
Section: Pharmacokinetic Sample Assessmentsmentioning
confidence: 99%